Analysis of the derformtion in induction triangle heating using laminated plate theory - Nguyen , Truong Thinh; Pham , Van Dieu (Journal of Technical Education Science, 2016)
Induction triangle heating for plate structures often results in produce various curved thick plate with some types of concave in shipyard industry. The problem of deformation in around an induction heating are being of major concern in shipyard industry. The induction heating induced deformation formulas for induction triangle heating, composed process parameters such as heat input, size of induction heating, velocity of inductor and plate’s thickness, are developed analytically by using the approximation of several rectangular cuboidal inclusions with eigenstrain in an infinite laminated theory. The source of deformation in induction process is the plastic strains which are caused by non-uniform temperature gradient. The distributions of plastic strain corresponding to eigenstrain are assumed by FEM solutions. In this paper, the formulas for plate deformation as transverse and longitudinal shrinkages as well as vertical deflection produced by induction triangle heating are formed based on eigenstrain concept using laminated plate theory to consider some cuboidal inclusions with eigeinstrain. The residual deformation that was due to thermal process was depends on the magnitude and region of plastic strains at heating affected zone. Comparison of the calculated results with experimental and finite element method (FEM) data shows the accuracy and validity of the proposal method.